Mechanical fatigue resistance of an implantable branched lead system for a distributed set of longitudinal intrafascicular electrodes. (10th November 2017) - Pena, A E; Kuntaegowdanahalli, S S; Abbas, J J; Patrick, J; Horch, K W; Jung, R
Abstract: Objective . A neural interface system has been developed that consists of an implantable stimulator/recorder can with a 15-electrode lead that trifurcates into three bundles of five individual wire longitudinal intrafascicular electrodes. This work evaluated the mechanical fatigue resistance of the branched lead and distributed electrode system under conditions designed to mimic anticipated strain profiles that would be observed after implantation in the human upper arm. Approach . Custom test setups and procedures were developed to apply linear or angular strain at four critical stress riser points on the lead and electrode system. Each test was performed to evaluate fatigue under a high repetition/low amplitude paradigm designed to test the effects of arm movement on the leads during activities such as walking, or under a low repetition/high amplitude paradigm designed to test the effects of more strenuous upper arm activities. The tests were performed on representative samples of the implantable lead system for human use. The specimens were fabricated using procedures equivalent to those that will be used during production of human-use implants. Electrical and visual inspections of all test specimens were performed before and after the testing procedures to assess lead integrity. Main results . Measurements obtained before and after applying repetitive strain indicated that all test specimens retained electrical continuity and that electrical impedance remained well below pre-specified thresholds for detection of breakage. Visual inspection under a microscope at 10×  magnification did not reveal any signs of damage to the wires or silicone sheathing at the stress riser points. Significance . These results demonstrate that the branched lead of this implantable neural interface system has sufficient mechanical fatigue resistance to withstand strain profiles anticipated when the system is implanted in an arm. The novel test setups and paradigms may be useful in testing other lead systems.